Conhecimento e atitude de mulheres gaúchas em relação à detecção precoce do câncer de mama - Alves, Pricilla Cândido (2015)
The study aimed to evaluate the effects of an educational intervention on knowledge and attitude of women from the Brazilian state of Rio Grande do Sul regarding early detection of breast cancer. Delineated study randomized controlled trial which was held at the Military Hospital of the Area of Porto Alegre and the Military Medical Services of Porto Alegre. The sample consisted of 182 women who attended to the data collection places for gynecological care, which were randomly allocated into two groups, with 91 belonging to the control group (CG) and 91 to the intervention group (IG). The criteria for inclusion were to be over 18. The exclusion criteria were to be illiterate women and cognitive impairment. Data collection occurred over a period of three months. The data collection instrument used was a semistructured interview guide adapted and validated. Data were analyzed using the Statistical Package for Social Sciences (SPSS) version 21.0 with the Mann-Whitney tests and the test of x2 Pearson in the analysis of the variables. The study was conducted after duly authorized by the Ethics Committee of the Federal University of Ceará (COMEPE-UFC) under the Protocol 369.590. The average age of participants was 46.4 years. The schooling level had an average of 15 years of education. The average income was R$ 4,357.89. The average age of menarche was 12.7 years. The average age of menopause was 48.5 years. The average age of first pregnancy was 23.15 years. The mean duration of breastfeeding was 12.16 months. The average length of contraceptive use was 137.52 months. Before the implementation of educational intervention, the initial assessment of knowledge demonstrated reduced suitability percentage, with only 6 (6.6%) participants in the GC with adequate knowledge about early detection of breast cancer. In the GI Pre Test there were 3 women (3.3%) with adequate knowledge. About the attitude there was a high percentage of adequacy, with the GC, 85 (93.4%) participants with proper attitude and in the GI, 84 (92.3%). The application of educational intervention produced 78% increase in suitability of knowledge in the GI Post Test when compared to the GI Pre Test and the GC. The adequacy of attitude increased by 7.8%. There was statistical significance when comparing the results for the GI Pre test and GI Post Test to knowledge (p = 0.001) and attitude (p = 0.007). The use of the information folder associated with brief motivational interviewing enabled the acquisition of knowledge and positive attitude of women for secondary prevention of breast cancer.